2006
DOI: 10.1111/j.1365-3156.2006.01587.x
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy and outpatient malaria case management among older children and adults in Kenya

Abstract: Summaryobjective To evaluate the accuracy of routine malaria microscopy, and appropriate use and interpretation of malaria slides under operational conditions in Kenya.methods Cross-sectional survey, using a range of quality of care assessment tools, at government facilities with malaria microscopy in two Kenyan districts of different intensity of malaria transmission. All patients older than 5 years presenting to outpatient departments were enrolled. Two expert microscopists assessed the accuracy of the routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
142
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(159 citation statements)
references
References 17 publications
15
142
1
1
Order By: Relevance
“…12 For example, in Tanzania and Kenya, sensitivity of 70% and specificity of 47-61% of clinical microscopy compared with expert readings has been observed. 13,14 Similar to our results, Kiggundu and others 15 reported sensitivity and specificity 95% following a brief refresher training program. However, their evaluation only included slides prepared 1 month after training.…”
Section: Discussionsupporting
confidence: 80%
“…12 For example, in Tanzania and Kenya, sensitivity of 70% and specificity of 47-61% of clinical microscopy compared with expert readings has been observed. 13,14 Similar to our results, Kiggundu and others 15 reported sensitivity and specificity 95% following a brief refresher training program. However, their evaluation only included slides prepared 1 month after training.…”
Section: Discussionsupporting
confidence: 80%
“…20,21 This finding has led to several attempts at retraining technicians to improve proficiency in malaria diagnosis. Refresher, in-service training of technicians needs to continue where appropriate for short-term needs.…”
Section: Emphasizing Pre-service Trainingmentioning
confidence: 99%
“…For example, Giemsa stain microscopy in selected district health laboratories in Kenya had a low sensitivity and specificity -69% and 62% respectively [14]. Other studies elsewhere have shown that Giemsa stain is more sensitive than field stain A and B, with suboptimal performance being attributed to the high workload and poor supervision of laboratory technicians [15].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the potential benefits of malaria microscopy are currently not realized because of the poor quality of routine testing [6,14]. For example, Giemsa stain microscopy in selected district health laboratories in Kenya had a low sensitivity and specificity -69% and 62% respectively [14].…”
Section: Discussionmentioning
confidence: 99%